Evaluation of Cognitive Status in Patients With and Without Previous Coronavirus Disease 2019 Infection - Toksoy, Cansu Köseoğlu; Gürsoy, Betül Kurtses (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of the study was to assess subjective cognitive function using the validated Cognitive Failures Questionnaire (CFQ) in patients with and without previous coronavirus disease 2019 (COVID-19) infection who presented to Afyonkarahisar Health Sciences University during COVID-19 pandemics. Methods: This study was conducted at Afyonkarahisar Health Sciences University between October 15, 2022, and November 15, 2022. In our study, the cognitive status of participants was assessed using the CFQ. The sample size was determined as 20-folds of the number of items in the CFQ. Results: Overall, 525 subjects were recruited to the study including 261 subjects with previous COVID-19 infection (49.7%) and 264 subjects without previous COVID-19 infection (50.2%). The mean CFQ score was 39.42 ± 16.3 and 30.05 ± 14.8 in the subjects with and without previous COVID19 infection, respectively. The CFQ score was found to be high in 105 (40.2%) of the subjects with previous COVID-19 infection and in 47 (17.8%) of subjects without previous COVID-19 infection. The mean CFQ score was 33.99 ± 13.4 in subjects with mild disease, 49.31 ± 14.8 in those with moderate disease, and 57.82 ± 15.4 in those with severe disease. Conclusion: Our results indicate that the COVID-19 infection had influence on cognitive status and that there was an association between disease severity and cognitive status. This study is important regarding raising awareness that COVID-19 survivors may experience problems in attention, memory, and clear thinking and emphasizing that there is need for systematic cognitive screening after the recovery of COVID-19. Cite this article as: Köseoğlu Toksoy C, Kurtses Gürsoy B. Evaluation of cognitive status in patients with and without previous Coronavirus Disease 2019 infection. Cerrahpaşa Med J. 2023;47(3):322-325.